L'autoévaluation accompagnée et contractualisée :Quelles retombées sur le développement professionnel?Ce qu'en disent les futurs enseignants et formateurs d'adultes - Bruno Perrault; Thérèse Levené
The study, led in French university context, is based on the observation that the writing of the professional dissertation by teachers and trainers of adults in higher education does not guarantee the development of a reflexive posture which regulates practices. Another way, little explored in adult education, is to consider the development of reflective thinking through self-assessment of practices. An accompanied and contractualized self-assessment device was tested during the 2016-2017 academic year by an audience of student future school teachers, adult trainers or training engineers. An analysis of content of interviews conducted after the experimentation with stakeholders highlights effects on reflexivity and more broadly on professional development. The results specify success factors for the self-assessment approach, invite to discussion and open up perspectives for student support.